IMB-0523 Inhibits Enterovirus 71 Replication by Activating Signal Transducer and Activator of Transcription 3 Signaling to Upregulate Interferon-Stimulated Genes Expression. Issue 1 (22nd January 2023) - Wang, Huiqiang; Ge, Miao; Li, Yanping; Li, Yuhuan; Li, Zhuorong
Abstract: Background: Hand, foot, and mouth disease caused by enterovirus 71 (EV71) infection is prevalent in the Asia-Pacific region in recent years. Currently, no drug is available for the prevention and treatment of EV71 infection. IMB-0523, a N -phenylbenzamide derivative, inhibits hepatitis B virus replication by upregulating the expression of APOBEC3G. In the present study, the effect of IMB-0523 on EV71 replication and related mechanism were investigated. Methods: The cytotoxicity of IMB-0523 was determined by cell counting kit. Quantitative real-time polymerase chain reaction and Western blot assay were used to detect the effect of IMB-0523 on EV71 replication and related mechanism. Cytopathic effect assay was used to investigate the effect of IMB-0523 on different EV71 strains, coxsackievirus A16, and coxsackieviruses of group B. Results: The results showed that IMB-0523 could dose-dependently inhibit EV71 replication. Preliminary mechanism studies showed that IMB-0523 could activate STAT3 signaling to upregulate the expression of interferon-stimulated genes to play an antiviral role. In addition, IMB-0523 inhibited the replication of different EV71 strains, coxsackievirus A16, and coxsackieviruses of group B. Conclusions: IMB-0523 inhibits EV71 replication by activating the STAT3 signaling pathway to upregulate interferon-stimulated gene expression. IMB-0523 has broad-spectrum antiviral potential and may be used as a lead compound for the development of broad spectrum antiviral drugs.